Elevated Fibronectin Levels in Profibrotic CD14+ Monocytes and CD14+ Macrophages in Systemic Sclerosis - Rudnik, Michał; Hukara, Amela; Kocherova, Ievgeniia; Jordan, Suzana; Schniering, Janine; Milleret, Vincent; Ehrbar, Martin; Klingel, Karin; Feghali-Bostwick, Carol; Distler, Oliver; Błyszczuk, Przemysław; Kania, Gabriela (Frontiers in Immunology, 2021)
Background Systemic sclerosis (SSc) is an autoimmune disease characterized by overproduction of extracellular matrix (ECM) and multiorgan fibrosis. Animal studies pointed to bone marrow-derived cells as a potential source of pathological ECM-producing cells in immunofibrotic disorders. So far, involvement of monocytes and macrophages in the fibrogenesis of SSc remains poorly understood. Methods & Results Immunohistochemistry analysis showed accumulation of CD14+ monocytes in the collagen-rich areas, as well as increased amount of alpha smooth muscle actin (alpha-SMA)-positive fibroblasts, CD68+ and mannose-R+ macrophages in the heart and lungs of SSc patients. The full genome transcriptomics analyses of CD14+ blood monocytes revealed dysregulation in cytoskeleton rearrangement, ECM remodelling, including elevated FN1 (gene encoding fibronectin) expression and TGF-β signalling pathway in SSc patients. In addition, single cell RNA sequencing analysis of tissue-resident CD14+ pulmonary macrophages demonstrated activated profibrotic signature with the elevated FN1 expression in SSc patients with interstitial lung disease. Peripheral blood CD14+ monocytes obtained from either healthy subjects or SSc patients exposed to profibrotic treatment with profibrotic cytokines TGF-β, IL-4, IL-10, and IL-13 increased production of type I collagen, fibronectin, and alpha-SMA. In addition, CD14+ monocytes co-cultured with dermal fibroblasts obtained from SSc patients or healthy individuals acquired a spindle shape and further enhanced production of profibrotic markers. Pharmacological blockade of the TGF-β signalling pathway with SD208 (TGF-β receptor type I inhibitor), SIS3 (Smad3 inhibitor) or (5Z)-7-oxozeaenol (TGF-β-activated kinase 1 inhibitor) ameliorated fibronectin levels and type I collagen secretion. Conclusions Our findings identified activated profibrotic signature with elevated production of profibrotic fibronectin in CD14+ monocytes and CD14+ pulmonary macrophages in SSc and highlighted the capability of CD14+ monocytes to acquire a profibrotic phenotype. Taking together, tissue-infiltrating CD14+ monocytes/macrophages can be considered as ECM producers in SSc pathogenesis.